2018
DOI: 10.24106/kefdergi.413389
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude Comparison of Gifted Students and Normal Peers on the Recycling and Environmental Effects

Abstract: Plastiklerin üretim artışı, geri dönüşüm ve depolamadaki yetersizlikler, bilinçsiz kullanım ve bertaraf alışkanlıkları, bu konuyu giderek daha önemli hale getirmeye başlamıştır. Bundan dolayı bu problemlerin çözümünde özellikle üstün yetenekli bireylere görev düşmektedir. Bu çalışmada Batı Karadeniz Bölgesinde bulunan Bilim ve Sanat Merkezlerinde (BİLSEM) öğrenim gören ulaşılabilen tüm ortaokul öğrencilerinin plastik atıkların geri dönüşümü ve çevreye etkileri konularında tutumları tarama yöntemiyle incelenmiş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Renzulli (1978), called the three-ring model, expresses giftedness as the intersection of above-average ability, task delivery, and creativity. Gifted individuals will form the intellectual segment in the society if their potential is evaluated correctly by giving appropriate trainings to them (Bakar et al, 2018). With appropriate trainings, it is inevitable that gifted individuals will contribute positively to the development of both their immediate environment and society (Sontay et al, 2014).…”
Section: Gifted Studentsmentioning
confidence: 99%
“…Renzulli (1978), called the three-ring model, expresses giftedness as the intersection of above-average ability, task delivery, and creativity. Gifted individuals will form the intellectual segment in the society if their potential is evaluated correctly by giving appropriate trainings to them (Bakar et al, 2018). With appropriate trainings, it is inevitable that gifted individuals will contribute positively to the development of both their immediate environment and society (Sontay et al, 2014).…”
Section: Gifted Studentsmentioning
confidence: 99%
“…Behrendt (2014) concluded that secondary school students had positive attitudes and awareness toward the concepts of travel about biological parks. Bakar (2013) stated that science and arts center secondary school students do not have enough behaviors to use the recycling bin, and environmental education is important for the prevention of environmental problems, environmental awareness, and attitude in his research. Aksan (2016) stated that recycling education increased the awareness of science teacher candidates about recycling and recyclable products in her study.…”
Section: Global Warmingmentioning
confidence: 99%
“…If we seek studies on recycling in the literature Katırcıoğlu (2019) found that field trip with recycling supports 7 th -grade students learning. Bakar (2013) concluded that science and arts center students have a low level of knowledge about the damage caused by plastic to the environment. Islam and his friends (2019) found that in their study waste should not be seen as a resource and we can be obtained from waste, environmental and economic benefits, reduction in CO2 emissions, and using energy will be decreased with recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Bir çalışmada, öğrencilerin yere çöp atma davranışı ile ilgili bir ölçek önerilmektedir [9]. Başka bir araştırmada çöpleri yere atma açısından Türkiye'de bulunan okul türleri (normal ve BİLSEM) öğrencileri arasında anlamlı bir farklılık görülmemektedir [10]. Bunun yanında ortaokul öğrencileri yere çöp atma davranışını en önemli çevre sorunu görmektedir [11].…”
unclassified